PENGARUH DESAIN PRODUK TERHADAP PROSES KEPUTUSAN PEMBELIAN KONSUMEN SEPEDA MOTOR HONDA SUPRA X : Survei pada Anggota Honda Astrea Supra Team Bandung - Agung Permadi, - (2007)
In the modern era just like now, the business competition has made the companies trying to winning the competition. Therefore they have to play modern marketing strategy concept which consumers oriented to take good market and to be the leader in the industry. The automotive industry were divided onto two kind of industry, four wheel automotive industry such as cars, etc and two wheel industry such as motorcycle. The motorcycle demand as large as the growth of population makes the motorcycle industry grow more and more, these situation effecting not only the world's economic growth but also Indonesia's economic growth. There's several name of company who role the motorcycle market share such as Honda, Yamaha, and Suzuki. Honda which is the leader of this business from many years ago have to face with new competitors, because of that Honda's market share as the leader were drowned about 3% or approximately 301.011 unit in January - mei 2006. From the Pre Survei data, this fenomena caused by Honda's product design (about 9,47% from total point of the product dimension) which is not better than the competitors product design Based on the problem statement, a research was conducted about The influence of product design towards buying decision process of Honda Supra X motorcycle. The object of this research are Honda Supra X motorcycle users which joined in to Honda Astrea Supra Team (HAST). The independent variable (X) are product design, such as shape, feature, durability, conformance quality, reability, easy to fixed, and style as the sub variables or indicator; and the dependent variable (Y) are buying decision process. The type of the research is descriptive verificative, and the method of the survey technique are systematic random sampling, with 100 respondent as a sample. The data used are from primary and secondary data, and the technique to analyze the data is multiple regression technique which using correlation coefficient, determination coefficient, F test and t test. The result of this research indicates that the influence of product design towards buying decision process are about 83,2%, and the rest of 16,8% was influenced by another causes. The biggest and significantly influence are came from durability, the second one is feature, style, easy to fixed, and shape. Therefore, The Company needs to increase their product design not only from those factors who has the biggest influence, but also from those who hasn't influenced such as conformance quality and reability as a Company marketing strategies in affecting buying decision process.